ORGANIZATION OF STUDENT’S INDEPENDENT WORK OF STUDENTS IN STUDYING THE GENERAL COURSE OF PHYSICS IN PHYSICAL SPECIALTIES OF HIGHER EDUCATIONAL INSTITUTIONS - Gamarnyk, Anna; Rachiy, Bohdan; Tadeusz, Olga; Yatsura, Mykhailo (Mountain School of Ukrainian Carpaty, 2020)
Independent work today remains the main means of obtaining deep fundamental knowledge by students and developing in them the desire to continuously acquire new knowledge, skills and abilities. The purpose of the work is to analyze the state of independent work of students in free economic education and the system of its organization and conducting during the study of the section "Optics" general physics course in physical specialties of Precarpathian National University named after Vasyl Stefanyk To achieve this goal, the following research methods were used: analysis of scientific and pedagogical literature, synthesis, generalization, systematization, which made it possible to clarify the features of the process of organizing independent work of students of physical specialties. Based on the theoretical analysis and the experience of the authors of the article, the organization and conduct of independent work of students in the process of studying the general course of physics in the "Optics" section, students of physical specialties concluded that: in the independent work of a student, one should understand any of his activities aimed at acquiring knowledge, skills and abilities necessary for him in his future professional activity; independent work of students is effective only if it is properly planned and organized, high-quality provision of its educational and methodological support with the widespread use of information technologies, independent work of a student will be successful only through the implementation of clear control over its implementation and its objective assessment by the teacher, the division of independent work into classroom and out-of-class work is purely conditional and has no basis whatsoever. The article considers the forms and methods of independent work of students, together with high-quality educational and methodological support of the educational process, practically form a certain training system, which should reveal the creative abilities of students, prepare them for an active search, and cause the need to improve their skills.